Proteomic Analysis of Post-synaptic Density Fractions from Shank3 Mutant Mice Reveals Brain Region Specific Changes Relevant to Autism Spectrum Disorder - Reim, Dominik; Distler, Ute; Halbedl, Sonja; Verpelli, Chiara; Sala, Carlo; Bockmann, Juergen; Tenzer, Stefan; Boeckers, Tobias M.; Schmeisser, Michael J. (Frontiers in Molecular Neuroscience, 2017)
Disruption of the human SHANK3 gene can cause several neuropsychiatric disease entities including Phelan-McDermid syndrome (PMS), autism spectrum disorder (ASD) and intellectual disability (ID). Although a wide array of neurobiological studies strongly supports a major role for SHANK3 in organizing the postsynaptic protein scaffold, the molecular processes at synapses of individuals harboring SHANK3 mutations are still far from being understood. In this study, we biochemically isolated the postsynaptic density (PSD) fraction from striatum and hippocampus of adult Shank3Δ11-/- mutant mice and performed ion-mobility enhanced data-independent label-free LC-MS/MS to obtain the corresponding PSD proteomes (Data are available via ProteomeXchange with identifier PXD005192). This unbiased approach to identify molecular disturbances at Shank3 mutant PSDs revealed hitherto unknown brain region specific alterations including a striatal decrease of several molecules encoded by ASD susceptibility genes such as the serine/threonine kinase Cdkl5 and the potassium channel KCa1.1. Being the first comprehensive analysis of brain region specific PSD proteomes from a Shank3 mutant line, our study provides crucial information on molecular alterations that could foster translational treatment studies for SHANK3 mutation-associated synaptopathies and possibly also ASD in general.